2021
DOI: 10.3389/fmicb.2021.669570
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Analysis Reveals Microecological Balance in the Emerging Rice–Crayfish Integrated Breeding Mode

Abstract: The interaction between the microbial communities in aquatic animals and those in the ambient environment is important for both healthy aquatic animals and the ecological balance of aquatic environment. Crayfish (Procambarus clarkii), with their high commercial value, have become the highest-yield freshwater shrimp in China. The traditional cultivation in ponds (i.e., monoculture, MC) and emerging cultivation in rice co-culture fields (i.e., rice–crayfish co-culture, RC) are the two main breeding modes for cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…Among the factors, the planting of rice may be especially important, as different crayfish-plant co-culture ecosystems have been shown to result in distinct bacterial communities in the intestines of crayfish ( Wei et al, 2021 ). The ecological interactions between the microbial communities in the intestines of crayfish and the environments cause variations in the gut microbiota composition between these two culture environments ( Wang et al, 2021 ). Nevertheless, bacterial communities that perform major functions in the guts of red swamp crayfish can change significantly, even at the phylum level.…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors, the planting of rice may be especially important, as different crayfish-plant co-culture ecosystems have been shown to result in distinct bacterial communities in the intestines of crayfish ( Wei et al, 2021 ). The ecological interactions between the microbial communities in the intestines of crayfish and the environments cause variations in the gut microbiota composition between these two culture environments ( Wang et al, 2021 ). Nevertheless, bacterial communities that perform major functions in the guts of red swamp crayfish can change significantly, even at the phylum level.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria play an important role in nutrient circulation, water quality maintenance, and the health of cultured animals [ 52 ]. In contrast to terrestrial animals, aquatic animals and microorganisms share the same water environment in the aquaculture ecosystem [ 53 ]. Therefore, aquatic animals are highly vulnerable to the changes in the surrounding bacterial community [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the pathogens, Vibrio and Pseudoalteromonas accounted for a relatively high proportion, and their proportion in the control pond was large and fluctuated significantly over time, while the proportion in the MC-treated pond was small. Vibrio and Pseudoalteromonas are considered opportunistic pathogenic bacteria [ 53 , 55 ], and opportunistic pathogenic bacteria are pervasive in seawater and become dominant when the aquaculture water quality deteriorates [ 7 , 56 ]. In fact, the high mortality of shrimp is attributed to the proliferation of opportunistic pathogenic bacteria [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA high-throughput sequencing approach has been used to assess the composition and diversity of bacterial communities in crayfish gut, water, or sediment in the RC model ( 16 20 ). Two previous studies have suggested that there was no significant difference in gut, water, and sediment microbiomes between the RC and crayfish monoculture (CM) models ( 18 , 19 ). Zhang et al suggested that overutilizing the RC model can lead to the destruction of soil microbial ecology ( 20 ).…”
Section: Introductionmentioning
confidence: 96%